(untitled) (Research, Society and Development, 2020)
Bruxism is defined as a parafunctional activity that can occur during the day and / or night. Its etiology is associated with different factors, such as morphological, pathophysiological and psychosocial. In the latter, anxiety, stress and depression can be mentioned, which are triggering agents that perpetuate the pathology. In view of the increasing prevalence of the aforementioned mental factors in the world population, and especially, among the young population, it is assumed that the bruxism resulting from these also accompanied the increase. This integrative review aimed to assess the association between bruxism and mental factors among adolescents. The bibliographic survey was carried out through the online access of the Virtual Health Library (VHL) and Pubmed (Medical Literature Analysis and Retrieval System on-line). The descriptors used were “adolescent”, “bruxism” and “risk factors”. The intersection between them was made with the Boolean digit AND between the search equation. As a filter it was considered: English, Portuguese and Spanish; and publications between the years 2011 to 2020. At the end of the search, seven articles were selected. The present work suggests a positive association between bruxism and mental factors such as anxiety, depression and stress in adolescents.